Antioxidant activities of extracts, methanol, and n-hexane partitions of cayenne pepper (Capsicum frutescens L.) - Slamet Slamet; Urmatul Waznah; Yusrilia Yusrilia (Media Farmasi: Jurnal Ilmu Farmasi, 2022)
Antioxidants are substances that can neutralize and/or stabilize free radicals. Cayenne pepper (Capsicum frutescens L.) is a natural source of antioxidants because it contains carotenoids, flavonoids, and vitamin C. This study aims to examine antioxidant activities of n-hexane, methanol, and extract of cayenne pepper (Capsicum frutescens L.) using the ferric reducing antioxidant power (FRAP) method. The extraction method was done by maceration, and the fractionation method was done by partitioning using unmixed solvents: methanol and n-hexane. The phytochemical screening test on extracts and partitions has discovered positive content of alkaloids, flavonoids, phenols, and terpenoids. Meanwhile, the TLC test used F254 silica gel as a stationary phase with chloroform: ethyl acetate as a mobile phase (6:4). The test discovered positive results containing flavonoids and phenols. Furthermore, the antioxidant activities were tested using the FRAP method with a UV-Vis spectrophotometer instrument at a maximum value of 598.05 nm and positive control of vitamin C. The results of measurement show that antioxidant activities are found in 505.67 ± 0.56 mol Fe2+/g of partition extract, 447.67 ± 16.2 mol Fe2+/g of methanol fraction, and 353± 5.29 mol Fe2+/g of n-hexane fraction.